Jatrorrhizine inhibits colorectal carcinoma proliferation and metastasis through Wnt/β-catenin signaling pathway and epithelial–mesenchymal transition - Wang P; Gao XY; Yang SQ; Sun ZX; Dian LL; Qasim M; Phyo AT; Liang ZS; Sun YF (Dove Medical Press, 2019)
Pan Wang,1 Xiao-Yan Gao,1 Si-Qian Yang,1 Zhi-Xin Sun,2,3 Lu-Lu Dian,1 Muhammad Qasim,1,4 Aung Thu Phyo,1,5 Zong-Suo Liang,1 Yan-Fang Sun11College of Life Sciences and Medicine, Zhejiang Sci-Tech University, Hangzhou 310018, People’s Republic of China; 2College of Life Sciences, Wenzhou Medical University, Wenzhou 325035, People’s Republic of China; 3Department of Life Sciences, Zaozhuang No.1 Middle School, Zaozhuang, 277100, People’s Republic of China; 4Institute of Sustainable Halophyte Utilization, University of Karachi, Karachi 75270, Pakistan; 5Department of Biotechnology, Mandalay Technological University, Mandalay 05072, MyanmarPurpose: Jatrorrhizine (JAT) is a natural protoberberine alkaloid, possesses detoxification, bactericidal and hypoglycemic activities. However, its anti-cancer mechanism is not clear. This study aimed to investigate the mechanism of JAT through which inhibits colorectal cancer in HCT-116 and HT-29 cells.Methods: MTT assay and colony formation assay were used to check the cell proliferation ability. Cell apoptosis and cell cycle were measured by Hoechst 33342 staining and flow cytometry, respectively. Cell migration and invasion were detected by scratch wound healing assay and trans-well assay, respectively. Further, expression of related proteins was examined via Western blotting and the in vivo anti-cancer effect of JAT was confirmed by nude mice xenograft model.Results: The research showed that JAT inhibited the proliferation of HCT-116 and HT-29 cells with IC50 values of 6.75±0.29 μM and 5.29±0.13 μM, respectively, for 72 hrs. It has also showed a time dependently, cell cycle arrested in S phase, promoted cell apoptosis and suppressed cell migration and invasion. In addition, JAT inhibited Wnt signaling pathway by reducing β-catenin and increasing GSK-3β expressions. Increased expression of E-cadherin, while decreased N-cadherin, indicating that JAT treatment suppressed the process of cell epithelial–mesenchymal transition (EMT). In HCT-116 nude mice xenograft model, JAT inhibited tumor growth and metastasis, and induced apoptosis of tumor cells.Conclusion: This study demonstrated that JAT efficiently inhibited colorectal cancer cells growth and metastasis, which provides a new point for clinical treatment of colorectal cancer.Keywords: jatrorrhizine (JAT), colorectal cancer (CRC), Wnt/β-catenin signaling, epithelial-mesenchymal transition (EMT), xenograft model